Virtual education and student learning in the Aesthetics and Cosmetology Program - Farfán Muentes, Maria Esther (2025)
This research aimed to identify students’ perceptions of the use of virtual education as a pedagogical tool in professional training within the Integral Aesthetics program at Universidad San Gregorio de Portoviejo (USGP). The methodology followed a quantitative, descriptive, and cross-sectional approach. A survey was administered to fourth-semester students. The results showed that virtual education has become firmly established in the Integral Aesthetics program, with high levels of student acceptance. However, diverse perceptions were identified regarding its impact, particularly in the development of practical skills. This confirms that virtual learning does not offer a homogeneous experience for all students. Therefore, it is necessary to implement differentiated pedagogical strategies and combine virtual education with in-person practice.